The mise en abyme in The Drowned World by James G. Ballard - Juan Varo Zafra (Miscelánea: A Journal of English and American Studies)
At the beginning of the 1960s, the New Wave of British science fiction sought to revitalise the genre by incorporating more contemporary themes (drugs, sex, criticism of consumerist society and the media) as well as new narrative and expressive formulas, with the aim of entering the mainstream. James G. Ballard was a forerunner of this trend thanks to a series of stories and experimental novels that embraced the worldviews of surrealism, situationism and nouveau roman. The mise en abyme, a recurring technique in this new body of work, was incorporated into the early novels by Ballard, a process which culminated with The Drowned World, in which the technique became highly complex. This article examines the three cases of mise en abyme in the novel, beginning with a theoretical discussion of this literary device, adding a certain Heideggerian approach related to the image of the world in art. The article then goes on to analyze in detail the paintings that operate as mises en abyme in the novel, classifying them and reflecting on their relationship with the work as a whole and the reader, as well as the significance in the renewing context of science fiction of the decade.